Enhancing Phantom Limb PainRehabilitation Technology withUser-Centered Improvements - Moberg, Oliver (My University, 2024)
Abstract Phantom limb pain (PLP) is a common and distressing sensation experienced by 50−85% of individuals with limb loss, often manifesting as pain in the removed body part without any physical cause. Rehabilitation methods such as mirror therapy, motor imagery, and phantom motor execution (PME) are used to alleviate this pain. PME, in particular, engages the central and peripheral nervous systems to activate muscles in the residual limb. Integrum AB has developed Neuromotus, a medical device for PLP rehabilitation that leverages PME principles through virtual reality (VR), augmented reality (AR), and serious gaming. This project aims to identify and implement user-centered improvements to Neuromotus. The project began with a qualitative pre-study involving semi-structured interviews with experienced therapists who have used Neuromotus in clinical practice. Based on their feedback, several improvements were identified and implemented. Including two new open-source games, enhanced functionalities in existing games, the addition of a proportional controller, and the ability to customize the AR limb skin tone. Stakeholders subsequently tested these enhancements and validation tests were made for all then new functionalities. The results indicate that the proportional controller significantly enhanced gameplay, while the customizable limb color in the AR environment promoted inclusiveness and ensured alignment with ethical standards. These improvements could collectively contribute to a more effective and user-friendly PLP rehabilitation experience.
Keywords: Keywords: Phantom Limb Pain, Phantom Motor Execution, Neuromotus, Augmented Reality, Serious Gaming.